No Viral No Justice: A Criminological Review of Social Media-Based Law Enforcement from the Perspective of Progressive Law - Runturambi, Arthur Josias Simon; Aswindo, Munarni; Meiyani, Eliza (Magister of Law, Faculty of Law, University of Mataram, 2024)
The phenomenon of